PENDEKATAN MATEMATIKA REALISTIK UNTUK MENGOPTIMALKAN PEMAHAMAN KONSEP MATEMATIS SISWA [REALISTIC MATHEMATICS EDUCATION TO OPTIMIZE STUDENTS’ UNDERSTANDING OF MATHEMATICAL CONCEPTS] - Yonathan, Andrew Billy; Seleky, Jacob Stevy (JOHME: Journal of Holistic Mathematics Education, 2023)
Understanding mathematical concepts is one of the competencies in learning mathematics, but not all students possess this competency yet. To address this problem, the author implemented realistic mathematical education (RME) in mathematics learning to optimize students’ understanding of mathematical concepts. The purpose of the RME implementation was to optimize students’ mathematical concepts understanding. The research method used was a descriptive qualitative method, namely by examining an object in its natural condition. The implementation of RME in mathematics learning uses real-life problems by actively conditioning students to construct their understanding of mathematical concepts, while teachers play an active role as facilitators. The results showed that the implementation of RME in mathematics learning can optimize students’ understanding of mathematical concepts. Thus, it can be concluded that the implementation of RME in mathematics learning can optimize students' understanding of mathematical concepts.BAHASA INDONESIA ABSTRACT: Pemahaman konsep matematika merupakan salah satu kompetensi dalam pembelajaran matematika, tetapi kompetensi tersebut belum dimiliki oleh semua siswa. Terkait permasalahan tersebut, penulis menerapkan pendidikan matematika realistis (PMR) dalam pembelajaran matematika untuk mengoptimalkan pemahaman konsep matematis siswa. Oleh karena itu, tujuan dari makalah ini adalah untuk menjelaskan implementasi PMR untuk mengoptimalkan pemahaman konsep matematis siswa. Metode penelitian yang digunakan adalah metode kualitatif deskriptif, yaitu dengan meneliti suatu objek dalam kondisi alaminya. Implementasi PMR dalam pembelajaran matematika menggunakan masalah kehidupan nyata dengan secara aktif mengkondisikan siswa untuk mengkonstruksi pemahaman konsep matematisnya, sedangkan guru berperan aktif sebagai fasilitator. Hasil penelitian menunjukkan implementasi PMR dalam pembelajaran matematika dapat mengoptimalkan pemahaman konsep matematis siswa. Dengan demikian, dapat disimpulkan bahwa implementasi PMR dalam pembelajaran matematika dapat mengoptimalkan pemahaman konsep matematis siswa.